The Effect of Service Quality of Motor Vehicle Testing UPT on Public Satisfaction of “KIR” Test Users at the Indramayu Regency Transportation Service - Zaini, Abdullah; Rohadin, Rohadin; Kurniawan, Zuki (Jurnal Abdimas, 2025)
This study aims to analyze the influence of service quality at the Motor Vehicle Inspection (KIR) Technical Implementation Unit (UPT) on the level of public satisfaction among service users at the Indramayu Regency Transportation Agency. The research background stems from the Transportation Agency's strategic role as a public agency providing essential services to ensure the safety and roadworthiness of motor vehicles on the highway. However, various public complaints indicate shortcomings in terms of service speed, officer accuracy, and the availability of infrastructure. The approach used was a quantitative descriptive explanatory survey method, involving 40 respondents from the public who used the KIR inspection service. Data were obtained through questionnaires, observation, and documentation. Data were then analyzed using validity, reliability, correlation, coefficient of determination, and t-tests to determine the significance of the relationships between variables. The results indicate that service quality has a positive and significant influence on public satisfaction. Service dimensions, including reliability, responsiveness, assurance, empathy, and tangibles, significantly contribute to increased public satisfaction. The correlation analysis revealed a strong relationship between service quality and satisfaction, while the coefficient of determination indicates that the majority of the variation in public satisfaction is explained by the service quality variable. These findings indicate that improving the quality of public transportation services depends not only on the availability of physical facilities, but also on the professionalism of the apparatus and the speed of response to public needs. Improved services at the Technical Implementation Unit (UPT KIR) are expected to encourage the realization of a safe, orderly, and satisfactory regional transportation system for the public.